Explaining the gender wage gap on the regional level in Russia - Maslova, Alena; Kalíšková, Klára; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
This diploma thesis is dedicated to the topic of the gender pay gap in the Russian Federation, its evolution, and the reasoning behind it. The gender pay gap was calculated for two periods on a regional level within a ten years difference. The period between the years 2000 and 2017 was analyzed. All custom calculations in this thesis were performed using data from the Russian Longitudinal Monitoring Survey – Higher School of Economics (RLMS-HSE), which was enriched by the dataset with regional statistics from the Federal State Statistic Service of the Russian Federation. The results of the analysis showed that the size of the gender pay gap varies across regions within the 40 % level. The linear model has proved that an increase in the childcare availability level by 1 % causes a decrease in the gender wage gap in the following periods by 0,71 % ceteris paribus. This output corresponds to the findings in the previous researches.
Vedoucí práce: Klára Kalíšková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses